2-Amino 4-methylpyridinium 3-chlorobenzoate – A phase matchable organic nonlinear optical material for optoelectronics device applications. (1st September 2017) - Babu, B.; Chandrasekaran, J.; Thirumurugan, R.; Anitha, K.; Saravanabhavan, M.
Highlights: The grown 2A4M3CB exhibits phase matching property. The 2A4M3CB is thermally stable up to 184 °C. 2A4M3CB exhibits a high optical transmittance, and lower dielectric constant values. Abstract: 2-Amino 4-methylpyridinium 3-chlorobenzoate (2A4M3CB) was synthesized and good quality single crystals of the size of 8 × 2 × 1.2 mm 3 were harvested from methanol by the slow evaporation solution growth technique at ambient temperature. Single crystal XRD reveals that 2A4M3CB crystallized in monoclinic system with the noncentrosymmetric space group P 21 . The crystalline phases and functional groups of 2A4M3CB have been identified and confirmed through powder X-ray diffraction and Fourier transform infrared (FTIR) studies, respectively. 1 H and 13 C NMR were recorded to interpret the molecular structure. The optical transmittance window and the lower cutoff wavelength of the 2A4M3CB have been identified by UV–Vis–NIR studies. Thermal and mechanical stability of the 2A4M3CB crystals were explained by TG/DTA and Vickers hardness analysis. Charge transport mechanism and photo response properties were analyzed through dielectric and photoconductivity studies. Powder second harmonic generation (SHG) characteristics and phase matching ability were explored by Kurtz and Perry powder SHG technique.